2022
DOI: 10.3390/antibiotics11060783
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Resistance to Antibiotics and Clonal Spread in COVID-19-Positive Patients on a Tertiary Hospital Intensive Care Unit, Czech Republic

Abstract: This observational retrospective study aimed to analyze whether/how the spectrum of bacterial pathogens and their resistance to antibiotics changed during the worst part of the COVID-19 pandemic (1 November 2020 to 30 April 2021) among intensive care patients in University Hospital Olomouc, Czech Republic, as compared with the pre-pandemic period (1 November 2018 to 30 April 2019). A total of 789 clinically important bacterial isolates from 189 patients were cultured during the pre-COVID-19 period. The most fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This may be due to the high severity of the clinical condition of critical COVID-19 patients, who may have been colonized easily and quickly by hospital pathogens. The spread of multi-drug resistant clones in the hospital environment that has been adapted to the dramatic wave of a viral pandemic is also likely to play a role [73]. This conjecture is supported by the results of microbiological findings in HAP patients with a high prevalence of multi-drug-resistant Enterobacterales strains.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This may be due to the high severity of the clinical condition of critical COVID-19 patients, who may have been colonized easily and quickly by hospital pathogens. The spread of multi-drug resistant clones in the hospital environment that has been adapted to the dramatic wave of a viral pandemic is also likely to play a role [73]. This conjecture is supported by the results of microbiological findings in HAP patients with a high prevalence of multi-drug-resistant Enterobacterales strains.…”
Section: Discussionmentioning
confidence: 82%
“…However, environmental issues also play a significant role. Previous studies by our authors' team, utilizing genetic methods, demonstrated clonal spread of identical bacterial strains in the ICU during the pandemic, leading to exogenous nosocomial infections, including respiratory tract infections caused by Klebsiella pneumoniae, Serratia marcescens, and Burkholderia cepacia complex, as well as colitis caused by Clostridioides difficile [72,73]. The reasons for this can be attributed to the predominantly open-space layout of the ward, where most rooms are open-plan, with few enclosed spaces for the isolation of patients, many of whom were connected to an HFOT device via a nasal mask.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The included studies were published from 2020 to 2022 from regions of Africa (Egypt) ( Ramadan et al, 2020 ), America (United States, Peru, and Brazil) ( Baggs et al, 2022 ; Copaja-Corzo et al, 2021 ; da Costa et al, 2022 ; Kubin et al, 2021 ; Nori et al, 2021 ), Asia (Pakistan, Saudi Arabia, Qatar, India, Iran, Iraq, China, Indonesia, and Korea) ( Ahmed et al, 2022 ; Alqahtani et al, 2022 ; Baiou et al, 2021 ; Bazaid et al, 2022 ; Bhaskaran, 2022 ; Boorgula et al, 2022 ; Jabir, 2022 ; Jamnani et al, 2022 ; Khurana et al, 2021 ; Li et al, 2020 ; Mahmoudi, 2020 ; Moradi et al, 2021 ; Palanisamy et al, 2021 ; Pourajam et al, 2022 ; Rao et al, 2022 ; Rizvi et al, 2022 ; Said et al, 2022 ; Sathyakamala, Peace & Shanmugam, 2022 ; Sharifipour et al, 2020 ; Sharma et al, 2021 ; Sinto et al, 2022 ; Son et al, 2021 ; Vijay et al, 2021 ; Zeshan et al, 2022 ) and Europe (Turkey, United Kingdoms, Italy, France, Czech Republic, Switzerland, Germany, Greece, and Spain) ( Bahce, Acer & Ozudogru, 2022 ; Baskaran et al, 2021 ; Bentivegna et al, 2021 ; Ceccarelli et al, 2022 ; Contou et al, 2020 ; Cultrera et al, 2021 ; Doubravska et al, 2022 ; Floridia et al, 2022 ; Fontana et al, 2021 ; Foschi et al, 2021 ; Gysin et al, 2021 ; Karataş et al, 2021 ; Karruli et al, 2021 ; Lingscheid et al, 2022 ; Mazzariol et al, 2021 ; Posteraro et al, 2021 ; Protonotariou et al, 2021 ; Suarez-de-la-Rica et al, 2021 ; Temperoni, Caiazzo & Barchiesi, 2021 ...…”
Section: Resultsmentioning
confidence: 99%
“…The causative organism was initially reported as K. pneumoniae , but genetic analysis revealed that it was indeed K. variicola . K. variicola have been reported among patients with immunocompromising conditions such as malignancy and diabetes [ 6 ], and a recent study in Czech Republic reported that the percentage of K. variicola as an etiological agent causing nosocomial infections increased significantly (from 1 to 6%, p = 0.0004) in COVID-19 patients compared to the pre-COVID-19 period [ 9 ]. But the impact of co-infection or secondary infection among COVID-19 patients remain uncertain.…”
Section: Discussionmentioning
confidence: 99%